Variability of the Middle Meningeal Artery Subject to the Shape of Skull - Kornieieva, Maryna; Hadidy, Azmy; Zhuravlova, Iuliia (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives Endovascular embolization of the middle meningeal artery (MMA) is currently considered one of the basic methods to treat acute bleeding and a posttraumatic aneurysm. The present research correlates the morphological characteristics of the MMA with individual skull shape.Design A prospective cohort study.Setting Hospital of University of Jordan (Amman, Jordan) from 2012 to 2013.Participants A total of 50 patients without known vascular pathology in the carotid system underwent routine magnetic resonance angiography examination of the head and neck.Main Outcome Measures The length and outer diameter of extracranial, intraosseous, and intracranial segments of the MMA were measured in patients with dolichocephalic, mesocephalic, and brachycephalic types of skulls.Results The brachycephalic patients have the most inauspicious anatomical precondition for endovascular intervention of the MMA due to the narrowest lumen of the vessel, high probability of a tortuous extracranial part, and pronounced inflexion at the transmission of the intraosseous segment to the intracranial one.Conclusions The morphological characteristics of the MMA have a close correlation with individual skull shape.
Keywords: middle meningeal artery; endovascular embolization; posttraumatic aneurism